2005
DOI: 10.1002/ca.20254
|View full text |Cite
|
Sign up to set email alerts
|

Forces necessary for the disruption of the cisternal segments of cranial nerves II through XII

Abstract: Manipulation of the cisternal segment of cranial nerves is often performed by the neurosurgeon. To date, attempts at quantifying the forces necessary to disrupt these nerves in situ, to our knowledge, has not been performed. The present study seeks to further elucidate the forces necessary to disrupt the cranial nerves while within the subarachnoid space. The cisternal segments of cranial nerves II through XII were exposed in six unfixed cadavers, all less than 6 hr postmortem. Forces to failure were then meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…[12][13][14] One study quantifying the forces in situ over the cranial nerves of unfixed cadaveric heads found that the minimal force causing a mechanical failure of the third nerve was between 0.22 and 0.3 N on the right side and between 0.3 and 0.61 N on the left side. 22 These values fall in lower intervals of forces compared with those encountered in our study, probably as a result of the difference in the quality of fixed and unfixed specimens. Even though it would be inaccurate to directly extrapolate the absolute calculated tension to live conditions, the aim of our cadaveric study was to elucidate the pure mechanical response of the nerve before and after its transcavernous mobilization in a geometrical setting almost identical to that of real surgery.…”
Section: Biomechanics Of the Oculomotor Nervecontrasting
confidence: 48%
“…[12][13][14] One study quantifying the forces in situ over the cranial nerves of unfixed cadaveric heads found that the minimal force causing a mechanical failure of the third nerve was between 0.22 and 0.3 N on the right side and between 0.3 and 0.61 N on the left side. 22 These values fall in lower intervals of forces compared with those encountered in our study, probably as a result of the difference in the quality of fixed and unfixed specimens. Even though it would be inaccurate to directly extrapolate the absolute calculated tension to live conditions, the aim of our cadaveric study was to elucidate the pure mechanical response of the nerve before and after its transcavernous mobilization in a geometrical setting almost identical to that of real surgery.…”
Section: Biomechanics Of the Oculomotor Nervecontrasting
confidence: 48%
“…Afterward, it courses in the lateral wall of the cavernous sinus below the CN III [13]. Laboratory investigation showed that the mechanical forces necessary to disrupt the CN III were larger, compared to the trochlear nerve [14]. In contrast, compared to the CN III, the trochlear nerve is less frequently impaired in patients with pituitary adenomas [2], [4].…”
Section: Discussionmentioning
confidence: 99%
“…The oculomotor and abducens nerves are amongst the most resilient cranial nerves, requiring considerably higher forces to result in functional impairment [5]. Several mechanisms exist by which intracranial air can develop enough disruptive strength to cause direct cranial nerve compression.…”
Section: Discussionmentioning
confidence: 99%